Is development really the best contraceptive?: A 20-year trial in Comilla District, Bangladesh - Barkat-E-Khuda; Sarah F. Harbison; Warren C. Robinson (Asia-Pacific Population Journal, 1990)
The present generally accepted theoretical approach to understanding fertility sees population and development as mutually interacting; that is, fertility affects development and development affects fertility as well. The effect of high fertility and rapid population growth on development goals has been well-understood since Coale and Hoover’s pioneering effort in 1958, but the notion that development programmes, other than family plannin programmes as such, affect fertility is a somewhat newer and more novel idea.